The Membrane Cholesterol Modulates the Interaction Between 17-βEstradiol and the BK Channel - Granados, Sara T.; Latorre, Ramon; Torres, Yolima P. (Frontiers in Pharmacology, 2021)
BK channels are composed by the pore former  subunit and, in some tissues, is associated with different accessory  subunits. These proteins modify the biophysical properties of the channel, amplifying the range of BK channel activation according to the physiological context. In the vascular cells, the pore former BK subunit is expressed with the 1 subunit, where they play an essential role in the modulation of arterial tone and blood pressure. In eukaryotes, cholesterol is a structural lipid of the cellular membrane. Changes in the ratio of cholesterol content in the plasma membrane (PM) regulates the BK channel activation altering its open probability, and hence, vascular contraction. It has been shown that the estrogen 17-Estradiol (E2) causes a vasodilator effect in vascular cells, inducing a leftward shift in the V0.5 of the GV curve. Here, we evaluate whether changes in the membrane cholesterol concentration modify the effect that E2 induces on the BK/1 channel activity. Using binding and electrophysiology assays after cholesterol depletion or enrichment, we show that the cholesterol enrichment significantly decreases the expression of the  subunit, while cholesterol depletion increased the expression of that  subunit. Additionally, we demonstrated that changes in the membrane cholesterol cause the loss of the modulatory effect of E2 on the BK/1 channel activity, without affecting the E2 binding to the complex. Our data suggest that changes in membrane cholesterol content could affect structural channel properties related to the E2 effect on BK/1 channel activity. Finally, the results suggest that an optimal membrane cholesterol content is essential for the activation of BK channels through the 1 subunit.